2018
DOI: 10.1200/jco.18.00606
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Localized Prostate Cancer: ASCO Clinical Practice Guideline Endorsement of an American Urological Association/American Society for Radiation Oncology/Society of Urologic Oncology Guideline

Abstract: Purpose In April 2017, the American Urological Association, American Society for Radiation Oncology, and Society of Urologic Oncology released a joint evidence-based practice guideline on clinically localized prostate cancer. The American Society of Clinical Oncology (ASCO) has a policy and set of procedures for endorsing clinical practice guidelines that have been developed by other professional organizations. Methods The Clinically Localized Prostate Cancer guideline was reviewed for developmental rigor by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
102
3
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(117 citation statements)
references
References 20 publications
0
102
3
12
Order By: Relevance
“…This difference, even after adjusting for dissimilarities in mortality due to other causes, remains the highest in the United States, which was more inflated in Caucasians compared to African-Americans (92.4% versus 85.8%). These variations are due to reasons such as differences in treatment care and the stages of the diagnosed disease [65,66]. In another study by Steele et al, conducted in 2017, the results showed that the survival rates of one and five-year were significantly higher than the findings of the present study in the years 2002-2003 and 2004-2009. In the former study, the one-year survival rate for both periods was 98.6 and 98.8, while in the present study, this rate was 81%.…”
Section: Discussioncontrasting
confidence: 71%
“…This difference, even after adjusting for dissimilarities in mortality due to other causes, remains the highest in the United States, which was more inflated in Caucasians compared to African-Americans (92.4% versus 85.8%). These variations are due to reasons such as differences in treatment care and the stages of the diagnosed disease [65,66]. In another study by Steele et al, conducted in 2017, the results showed that the survival rates of one and five-year were significantly higher than the findings of the present study in the years 2002-2003 and 2004-2009. In the former study, the one-year survival rate for both periods was 98.6 and 98.8, while in the present study, this rate was 81%.…”
Section: Discussioncontrasting
confidence: 71%
“…Both LDR-EBRT and HDR-EBRT are recommended as treatments for men with intermediate and high risk PCa by American Society of Clinical Oncology (ASCO), American Brachytherapy Society, National Institute for Health and Care Excellence (NICE) and European Association of Urology [24][25][26][27][28]. No RCTs directly comparing LDR-EBRT with HDR-EBRT have been reported, although one is currently in progress (ClinicalTrials.gov Identifier NCT03426748).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, enough time for follow-up was necessary to compare the prostatectomy group and observation group. The incidental discovery of low-grade prostate cancer patients is not likely to shorten survival or cause health problems during a man's lifetime (25), and guidelines on the use of observation or active surveillance in men with clinically insignificant prostate cancer were described (26)(27)(28). risk stratification for localized prostate cancer patients is necessary.…”
Section: Discussionmentioning
confidence: 99%